Postharvest Loss Assessment of Tomato in Selected Locations of Bangladesh (Bangladesh Journal of Agricultural Research, 2022)
Tomato is a very well-known horticultural crop in Bangladesh. In order to make tomato production profitable postharvest management is very important. The present study assessed tomato postharvest losses in four intensive growing sites of Jamalpur and Rangpur districts of Bangladesh. Farm level postharvest losses were measured through using descriptive and inferential statistics. Cobb- Douglas type multiple linear regression model was used to identify the factors affecting farm level tomato postharvest loss in the survey areas. Farm level postharvest loss of tomato was 12.45% per farm in the survey area. From this3.59% was due to partial damages and the rest 8.86% was for full damages of tomato. The major causes for postharvest loss of tomato were rotten, disease and insect infestation. This loss incurs financial loss at farm level by BDT 152.45 per decimal of tomato cultivation. Total harvested amount, family member and selling price were some of the important factors for tomato postharvest loss in the survey area. Wide practices of improved postharvest management practices are essential to reduce tomato postharvest loss in the survey area.Bangladesh J. Agril. Res. 45(1): 43-52, March 2020